(untitled) (BIRDEM Medical Journal, 2013)
Objective: To compare the haemodynamic effect of thiopental/fentanyl with etomidate/fentanyl during anaesthetic induction in patients with coronary artery disease with poor left ventricular function (ejection fraction < 45%). Design: A retrospective randomized trial. Setting: Ibrahim Cardiac Hospital and Research Institute. Participants: Twenty patients with coronary artery disease of poor left ventricular function (ejection fraction<45%) scheduled for elective coronary artery bypass surgery. Interventions: Patients were allocated randomly to receive either thiopental/fentanyl or etomidate/fentanyl for induction. Measurement & Main Results: Haemodynamic response (heart rate, mean arterial pressure) were recorded at 1 minute interval starting from induction till five minutes after intubations. The reduction of mean arterial pressure was greater in patients who received thiopental/fentanyl induction (maximal decrease 32%) in comparison to etomidate/fentanyl induction (maximal decrease12%) [P<0.05 which is statistically significant]. The changes of heart rate were insignificant between the groups (reduction of heart rate 8% versus 7%). Conclusion: Etomidate/ fentanyl induction reduces less blood pressure in comparison to thiopental/fentanyl induction in patients of poor left ventricular function but changes of heart rate were insignificant in between the groups. Birdem Med J 2013; 3(1): 23-26 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17123